2015
DOI: 10.1016/j.molcel.2015.09.025
|View full text |Cite
|
Sign up to set email alerts
|

PEPCK Coordinates the Regulation of Central Carbon Metabolism to Promote Cancer Cell Growth

Abstract: Summary Phosphoenolpyruvate carboxykinase (PEPCK) is well known for its role in gluconeogenesis. However, PEPCK is also a key regulator of TCA cycle flux. The TCA cycle integrates glucose, amino acid and lipid metabolism depending on cellular needs. In addition, biosynthetic pathways crucial to tumor growth require the TCA cycle for the processing of glucose and glutamine derived carbons. We show here an unexpected role for PEPCK in promoting cancer cell proliferation in vitro and in vivo by increasing glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
230
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(258 citation statements)
references
References 33 publications
12
230
2
2
Order By: Relevance
“…7F). These data are consistent with recent reports that glucose deprivation results in an increase in Pck expression (33, 34) which promotes metabolic flexibility when nutrients are limiting (35,36). Also, these data show the utility of assessing a phenotype across a series of genetic perturbations.…”
Section: Mpc Deficiency Promotes Metabolic Plasticity In Uterosupporting
confidence: 91%
“…7F). These data are consistent with recent reports that glucose deprivation results in an increase in Pck expression (33, 34) which promotes metabolic flexibility when nutrients are limiting (35,36). Also, these data show the utility of assessing a phenotype across a series of genetic perturbations.…”
Section: Mpc Deficiency Promotes Metabolic Plasticity In Uterosupporting
confidence: 91%
“…There are two isoforms of PCK: cytosolic PCK (PCK1) and a mitochondrial isoform of PCK (PCK2). PCK1, but not PCK2, was reported to be over-expressed in colorectal cancer and promotes tumour growth by increasing glucose and glutamine metabolism52. PCK2 expression was reported to be elevated in non-small-cell lung carcinoma (NSCLC) and is regulated by glucose and required for in vivo tumour growth53.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the mitochondrial isoform of PEPCK, PEPCK-M (also known as PCK2), which is expressed in breast and lung cancer cells, as well as in several other cancer cell lines, was reported to be increased and activated under limited glucose conditions 9597 . It was also reported that the cytosolic form of PEPCK, PEPCK-C (also known as PCK1) is overexpressed in colon cancer, and it accelerates the generation of glycolytic intermediates 98 . Surprisingly, cytoplasmic PEPCK-C also increased the use of glucose by a mechanism that may involve the activation of mTORC1 that is not fully understood.…”
Section: Reprogramming Of Glucose Metabolismmentioning
confidence: 99%